2016
DOI: 10.1152/advan.00017.2015
|View full text |Cite
|
Sign up to set email alerts
|

Peer-assisted learning: filling the gaps in basic science education for preclinical medical students

Abstract: In contrast to peer-assisted learning (PAL) in clinical training, there is scant literature on the efficacy of PAL during basic medical sciences teaching for preclinical students. A group of senior medical students aimed to design and deliver clinically oriented small-group tutorials after every module in the preclinical curriculum at a United Kingdom medical school. Twenty tutorials were delivered by senior students throughout the year to first- and second-year students. A baseline questionnaire was delivered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The importance of training for successful peer teaching has been supported by others (Lockspeiser et al, 2008; Lachman et al, 2013; Sammaraiee et al, 2016; Johansson et al, 2018), who suggest that selecting the star students as PTs may not be the best strategy for a successful program (Topping, 1996). Knowledge of neuroanatomy, alone, does not guarantee that a student will become a good PT.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The importance of training for successful peer teaching has been supported by others (Lockspeiser et al, 2008; Lachman et al, 2013; Sammaraiee et al, 2016; Johansson et al, 2018), who suggest that selecting the star students as PTs may not be the best strategy for a successful program (Topping, 1996). Knowledge of neuroanatomy, alone, does not guarantee that a student will become a good PT.…”
Section: Discussionmentioning
confidence: 93%
“…Peer‐tutors can be senior medical students, MSc or PhD students, or, when referring to a clinical setting, junior doctors, interns, residents, or clinical fellows. Most departments design a training program for the tutors in order to prepare them for their teaching role (Lachman et al, 2013; Aba Alkhail, 2015; Sammaraiee et al, 2016; Johansson et al, 2018). The success of these programs has been attributed to the ability of peer tutors and tutees to communicate more effectively and, therefore, create a more pleasant and productive learning environment (Allen and Boraks, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Although many people think the LBL teaching mode is not as good as other teaching modes [ 9 12 ], different teaching modes have different advantages. If the LBL teaching mode is used properly, the LBL teaching mode can provide maximum benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Sammaraiee et al demonstrated this resource application to basic science labs and Shiozawa, et al specifically showed improved student learning of dissection skills. 18,19 Resource limited nations such as Zambia could benefit greatly with PAL methodology in other lab areas to help with sustainability and encourage academic advancement for the trainers.…”
Section: Discussionmentioning
confidence: 99%